Sources of Dietary Protein in Relation to Blood Pressure in a General Dutch Population - Altorf - van der Kuil, Wieke; Engberink, Mariëlle F.; Vedder, Moniek M.; Boer, Jolanda M. A.; Verschuren, W. M. Monique; Geleijnse, Johanna M. (PLOS ONE, 2012)
Background Little is known about the relation of different dietary protein types with blood pressure (BP). We examined whether intake of total, plant, animal, dairy, meat, and grain protein was related to BP in a cross sectional cohort of 20,820 Dutch adults, aged 20–65 y and not using antihypertensive medication. Design Mean BP levels were calculated in quintiles of energy-adjusted protein with adjustment for age, sex, BMI, education, smoking, and intake of energy, alcohol, and other nutrients including protein from other sources. In addition, mean BP difference after substitution of 3 en% carbohydrates or MUFA with protein was calculated. Results Total protein and animal protein were not associated with BP (ptrend = 0.62 and 0.71 respectively), both at the expense of carbohydrates and MUFA. Systolic BP was 1.8 mmHg lower (ptrend<0.01) in the highest (>36 g/d) than in the lowest (<27 g/d) quintile of plant protein. This inverse association was present both at the expense of carbohydrates and MUFA and more pronounced in individuals with untreated hypertension (−3.6 mmHg) than in those with normal (+0.1 mmHg) or prehypertensive BP (−0.3 mmHg; pinteraction<0.01). Meat and grain protein were not related to BP. Dairy protein was directly associated with systolic BP (+1.6 mmHg, ptrend<0.01), but not with diastolic BP (ptrend = 0.24). Conclusions Total protein and animal protein were not associated with BP in this general untreated Dutch population. Plant protein may be beneficial to BP, especially in people with elevated BP. However, because high intake of plant protein may be a marker of a healthy diet and lifestyle in general, confirmation from randomized controlled trials is warranted.